FE Modelling of Optimization on Strengthening Glulam Timber Beams by using Compressed Wood Blocks. (2017) - Anshari, Buan; Guan, Zhongwei
Abstract: A new approach to strengthen glulam beams by using compressed wood was introduced by author. Compressed wood (CW) is made of a lower grade wood, which is densified in the radial direction under specific pressure and temperature conditions. In order to optimize the structural performance of glulam beams reinforced by compressed wood, in terms of load carrying capacity, strength and stiffness, parametric studies were carried out on thickness, depth and space of CW blocks. In this study, the dimensions of the beam models were 3800 mm in length, 120 mm in width and 200 mm in depth which comply with the requirements from Eurocode 5, and BS EN 408:2003, where the ratio between the span and the depth equals to 18. There are nineteen beams simulated in the parametric studies using validated FE models. The parameters covered in the simulations include the thickness, depth and spacing of CW blocks, however the CW block width and beam dimensions were remained unchanged. The results indicate that there are significant enhancements on the pre-camber (up to 1/288-deflection/span ratio), initial bending stiffness (up to 23.84%) for a beam reinforced by seven CW blocks with a thickness and depth of 50 mm and 95 mm respectively and ultimate load (increased to 10.4%) of glulam beams reinforced by seven CW blocks with thickness of 40 mm.